2009
DOI: 10.1093/europace/eup362
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of and outcomes from cardiac device related infections

Abstract: Cardiac device infection is a rare complication, with significant morbidity and mortality. Complete hardware removal with appropriate duration of antimicrobial therapy results in the best outcomes for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
132
3
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 21 publications
3
132
3
12
Order By: Relevance
“…A series without complete device removal have shown that over half of patients demonstrate relapse. 10,68,69 In a recent study, it was found that the rate of CIED infection after CIED extraction was higher in patients with incomplete lead removal, 13.5 % versus 3.0 %. 70 In addition, mortality appears higher without complete removal.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
“…A series without complete device removal have shown that over half of patients demonstrate relapse. 10,68,69 In a recent study, it was found that the rate of CIED infection after CIED extraction was higher in patients with incomplete lead removal, 13.5 % versus 3.0 %. 70 In addition, mortality appears higher without complete removal.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
“…It is extremely important to confirm LRIE in order to initiate adequate therapy, as in patients with this insidious entity, long-term had positive cultures from leads explanted transvenously through the infected pocket, although pocket cultures were negative, and vice versa, there were negative cultures from leads extracted transvenously through the pocket which was culture-positive (15%). 10 The Polish TLE registry provided similar data (1801 patients, including 746 with CDI): 11% of positive lead cultures were obtained from patients with the symptoms of PI, although pocket cultures were negative; 16.7% of negative lead cultures were concomitant with positive pocket cultures (unpublished data). In view of the low rate of discordance, positive lead cultures should be regarded as very helpful in the diagnosis of LRIE.…”
mentioning
confidence: 87%
“…The time of onset of the infection is extremely variable. Margey et al (2010) reported a median duration from device implant or revision to presentation with confirmed cardiac device infection of 150 days (range 5-2920 days, with an interquartile 25% of 35 days and an interquartile 75% of 731 days). Fever, chills and malaise were the most common presenting symptoms.…”
Section: Complications Of Pacemaker Implantation 273mentioning
confidence: 99%
“…Microbiological findings. It is not always possible to define the agent of infection: in a very recent report (Margey et al, 2010) out of 39 cardiac device infection cases, a causative organism was identified only in 62%. The most frequent causative organism was methicillin sensitive Staphyloccoccus aureus (30.8%), followed by coagulase negative Staphylococcus (20.5%), and Streptococcus species (7.7%).…”
Section: Complications Of Pacemaker Implantation 273mentioning
confidence: 99%
See 1 more Smart Citation